Listening to the forest and its curators: lessons learnt from a bioacoustic smartphone application deployment - Moran, Stuart; Pantidi, Nadia; Rodden, Tom; Chamberlain, Alan; Griffiths, Chloe; Zilli, Davide; Merrett, Geoff (ACM, 2014)
Our natural environment is complex and sensitive, and is home to a number of species on the verge of extinction. Surveying is one approach to their preservation, and can be supported by technology. This paper presents the deployment of a smartphone-based citizen science biodiversity application. Our findings from interviews with members of the biodiversity community revealed a tension between the technology and their established working practices. From our experience, we present a series of general guidelines for those designing citizen science apps